Pseudolaric acid B induces G2/M phase arrest in canine mammary tumor cells by targeting CDK1 - Chen, Mengjuan; Han, Hui; Qin, Mengke; Li, Huixin; Lu, Qiqi; Huang, Xin; Meng, Qingda; Xie, Shanshan (Frontiers in Veterinary Science, 2025)
IntroductionCurrent management of canine mammary tumors (CMTs) remains reliant on surgical resection and chemotherapy. However, these strategies are often limited by high recurrence rates and systemic toxicity. Addressing these limitations requires urgent development of safer and more effective therapeutics. Pseudolaric acid B (PAB), a bioactive compound extracted from the roots of the Pseudolarix kaempferi Gord., has garnered attention for its broad-spectrum antitumor activity and favorable pharmacokinetic profile, and it has shown promise in inhibiting the growth of a variety of tumors, including breast cancer. The aim of this study was to investigate the anticancer effects of PAB on canine mammary tumor U27 cells and its underlying mechanisms.Methods and resultsIn vitro analyses demonstrated that PAB dose dependently reduced cell viability, suppressed cell proliferation, and triggered caspase-mediated apoptosis. Transcriptomic profiling of PAB-treated tumor cells revealed significant enrichment of differentially expressed genes in pathways such as gap junction, cell cycle, and cellular senescence. Mechanistically, CDK1 suppression by PAB, achieved through binding that diminishes its expression and stability, induced G2/M phase arrest and halted mitotic progression. While these findings suggest the potential of PAB as a candidate for canine mammary tumor treatment, further investigations are warranted to delineate its precise in vivo targeting specificity and pharmacodynamic interactions.DiscussionThese findings not only expand the translational applicability of PAB in veterinary oncology but also identify CDK1 as a potential therapeutic vulnerability for combinatorial treatment strategies in CMTs.